2016
DOI: 10.1002/mabi.201500381
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Micelles for Targeted and Efficient Doxorubicin Delivery to Multidrug‐Resistant Breast Cancer Cells

Abstract: For efficient treatment of multidrug-resistance (MDR) breast cancer cells, design of biocompatible mixed micelles with diverse functional moieties and superior stability is needed for targeted delivery of chemical drugs. In this study, polypropylene glycol (PPG)-grafted hyaluronic acid (HA) copolymers (PPG-g-HA) are used to make mixed micelles with different amounts of pluronic L61, named PPG-g-HA/L61 micelles. Optimized PPG-g-HA/L61 micelles with 3% pluronic L61 exhibit great stability in aqueous solution, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Dox fluorescent signal at dsi-motif/Dox molar ratio of 1:1 was significantly reduced below 10% both at 24°C and at 37°C. More than 90% of initial Dox was intercalated within ds-i-motif, which is consistent to previous studies [17,18,22,24]. In this study, we used a one base pair mismatched DNA sequence (flare) as a complementary sequence for the i-motif.…”
Section: Intercalation and Ph-dependent Release Of Doxsupporting
confidence: 86%
See 1 more Smart Citation
“…Dox fluorescent signal at dsi-motif/Dox molar ratio of 1:1 was significantly reduced below 10% both at 24°C and at 37°C. More than 90% of initial Dox was intercalated within ds-i-motif, which is consistent to previous studies [17,18,22,24]. In this study, we used a one base pair mismatched DNA sequence (flare) as a complementary sequence for the i-motif.…”
Section: Intercalation and Ph-dependent Release Of Doxsupporting
confidence: 86%
“…Multi-drug-resistant breast cancer cells of the MCF-7 (MCF-7/MDR) cell line were maintained in RPMI 1640 supplemented with 10% FBS, 100 U/mL penicillin, and 100 lg/mL streptomycin at 37°C in a humidified atmosphere of 5% CO 2 , according to our previous study [22]. For the anti-proliferation study, cells were seeded at a density of 1 9 10 4 cells per well in a 96-well plate 24 h before treatment.…”
Section: Anti-proliferation Studymentioning
confidence: 99%
“…Past studies have shown that DOX not only inhibited DNA synthesis but also produced cytotoxic hydroxyl radicals. [ 19 ] Thus, intracellular ROS levels were further assessed by 2,7‐Dichlorodi‐hydrofluorescein diacetate (DCFH‐DA) probe. As shown in Figure a, bright green fluorescence was observed in MCF‐7 cells with treatment of free DOX or DOX‐NPs, indicating ROS generation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PPG-g-HA/L61 micelles were the most selective cytotoxic delivery system tested by Jung et al for the selective treatment of cancer cells. Furthermore, by mixing the functional pluronic L61 polymer with CD44-targeted PPG-g-HA copolymers, Jung et al were able to create a novel formulation that utilizes both the targeting strategy of HA and the ability of pluronic L61 to combat MDR cancers via ATP depletion [102]. …”
Section: Innovative Delivery Packagesmentioning
confidence: 99%